Development and Performance Assessment of a Novel Integrated MSBR for Sustainable Domestic Wastewater Treatment - Muhammad, Hanaa A.; Bakhtyar A. Othman,; Galawezh B. Bapeer, (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
This study presents a novel integrated modification of the Sequencing Batch Reactor (MSBR), combining the operational flexibility of conventional SBRs with the biomass retention and stability of a Moving Bed Biofilm Reactor (MBBR) through the incorporation of an upstream equalisation tank containing floating media and diffusers. The performance of the MSBR was evaluated against a conventional SBR and an MBBR under identical operating conditions. Over a 12-month monitoring period, influent and effluent samples were analysed for 25 physicochemical parameters representing organic load, nutrient dynamics, physical water quality, and mineral or trace element composition. Statistical analyses were conducted using IBM SPSS Statistics version 25. The MSBR consistently achieved the highest treatment performance. COD and BOD removal efficiencies reached 92.2% and 92.4%, compared with 88.5% and 88.7% in the MBBR and 82.6% and 82.9% in the SBR. Total nitrogen reduction was also higher in the MSBR (91.1%) than in the MBBR (79.9%) and SBR (85.7%), while total phosphorus removal reached 96%, outperforming both the MBBR (79.4%) and the SBR (89.5%). Sulfate removal remained moderate across all systems (MBBR 65.8%, MSBR 64.9%, SBR 57.1%). Although the SBR showed slightly higher oil and grease removal (83.4%), this marginal difference is outweighed by the MSBR’s superior nutrient and organic matter removal. Seasonal and monthly analyses confirmed the operational robustness of the MSBR. Overall, the results demonstrate that the integrated MSBR is a reliable and superior alternative for sustainable domestic wastewater treatment.